Pengaruh Pembelajaran TANDUR Berbantuan Mathlet GeoGebra terhadap Pemahaman Konsep Matematika ditinjau dari Kemampuan Visual - Ni Made Yuning Sari Parwati; Gede Suweken; I Gusti Putu Sudiarta (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
This research aimed to determine the effect of TANDUR learning assisted mathlet Geogebra on students’ mathematical conceptual understanding reviewed of students' visual abilities. The type of this research is a quasi-experimental with treatment by level designs on the topic of the Pythagorean theorems. The population of this research were 393 students spread in 10 classes in grade 8th of SMP N 12 Denpasar. The sample was determined using cluster random sampling technique. There were two data of this research, namely students’s mathematical conceptual understanding and students’ visual ability which were collected by essay and multiple choices test respectively. The data obtained were analyzed using t-test with significance level of 5%. The results showed that the students’ mathematical conseptual understanding who follows TANDUR learning assisted mathlet Geogebra was better than the students who follow the TANDUR learning only. The same results were also obtained for students with higher or lower visual abilities. However, students who have higher levels of visual abilities were easier to understand abstract mathematical concepts. Thus the TANDUR learning assisted mathlet Geogebra affect positively the students’s mathematical conceptual understanding in terms of students' visual abilities. Key words: TANDUR learning assisted mathlet Geogebra, mathematical conceptual understanding, Pythagorean theorems, and visual ability